Polybenzimidazole membranes functionalised with 1-methyl-2-mesitylbenzimidazolium ions via a hexyl linker for use in vanadium flow batteries. (12th June 2019) - Lee, Yona; Kim, Sangwon; Maljusch, Artjom; Conradi, Oliver; Kim, Hyoung-Juhn; Jang, Jong Hyun; Han, Jonghee; Kim, Jihyun; Henkensmeier, Dirk
Abstract: 1-(6-bromohexyl)-3-methyl-2-(2, 4, 6-trimethylphenyl)-2H-benzimidazolium bromide was synthesised and grafted onto polybenzimidazole (PBI). The highest obtained degrees of functionalisation were 0.7 and 1.1 ionic groups per repeat unit, corresponding to ion exchange capacities of 1.25 and 1.55 mmol chloride/g. While the latter material had much reduced tensile strength and Young's modulus, the material with a lower degree of functionalisation showed properties similar to PBI and was therefore further investigated. X-ray scattering showed that the functional group reduced the crystallinity. Conductivity was in the range of 2–3 mS cm −1, but increased to 23 mS cm −1 after doping in 2 M sulfuric acid, 2–4 times higher than for doped PBI. Permeability for VO 2+ ions was 0.8 × 10 −12 m 2 s −1 . In the vanadium redox flow battery, the grafted PBI showed higher coulomb and voltage efficiency than PBI, and therefore also higher energy efficiency. Graphical abstract: Image 1 Highlights: PBI was functionalised with hexyl tethered 1-methyl-2-mesityl-benzimidazolium ions. Highest reached ion exchange capacity was 1.55 mmol chloride/g. Conductivity of the 2 M sulfuric acid doped membrane was 23 mS cm −1 . Permeability for VO 2+ ions was 0.8 × 10 −12 m 2 s −1 CE, VE and EE were higher than for a cell using pristine PBI.